2018
DOI: 10.1016/j.jcrc.2017.08.046
|View full text |Cite
|
Sign up to set email alerts
|

Clinical management of pressure control ventilation: An algorithmic method of patient ventilatory management to address “forgotten but important variables”

Abstract: Pressure controlled ventilation is a common mode of ventilation used to manage both adult and pediatric populations. However, there is very little evidence that distinguishes the efficacy of pressure controlled ventilation over that of volume controlled ventilation in the adult population. This gap in the literature may be due to the absence of a consistent and systematic algorithm for managing pressure controlled ventilation. This article provides a brief overview of the applications of both pressure controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 6 publications
0
15
2
3
Order By: Relevance
“…In the A/C-pressure control ventilation mode, the inspiratory time tends to be within the range of 0.7 to 1.0 seconds. [ 30 ] However, in the present study, the median inspiratory time was 1.5 (1.3–1.5) seconds. In a recent study of ARDS patients, the end-inspiratory pause prolongation was reported to induce a significant decrease in the levels of PaCO 2 .…”
Section: Discussioncontrasting
confidence: 72%
“…In the A/C-pressure control ventilation mode, the inspiratory time tends to be within the range of 0.7 to 1.0 seconds. [ 30 ] However, in the present study, the median inspiratory time was 1.5 (1.3–1.5) seconds. In a recent study of ARDS patients, the end-inspiratory pause prolongation was reported to induce a significant decrease in the levels of PaCO 2 .…”
Section: Discussioncontrasting
confidence: 72%
“…Thus, some guidelines recommend initial inspiratory pressure settings as low as 5–10 cmH 2 O. 4 To help filter noise and fluctuating data, 10% of these values are used as the threshold to define what constitutes a ‘true’ breath. Hence, 10% of 400 mL (40 mL), 60 L/min (6 L/min) and 10 cmH 2 O (1 cmH 2 O) are listed as these criteria, which set very low thresholds and thus exclude relatively few breaths while ensuring those breaths captured are not influenced by partial breaths or coughs and asynchrony.…”
Section: Methodsmentioning
confidence: 99%
“…Одним із вірогідних пояснень такої різниці поміж застосовуваними режимами може бути мінімізація коливань рівня рСО 2 при застосуванні PRVC з контро-льованим хвилинним об'ємом вентиляції на противагу SIMV/PSV та РС, де дихальний об'єм є похідною величиною та може істотно коливатись при вентиляції в режимах із контрольованим тиском у дихальних шляхах при змінах комплаєнсу легень, що призводитиме до флуктуацій рСО 2 як у бік гіперкапнії, так і гіпокапнії. Своєю чергою, рівень рСО 2 відіграватиме одну з провідних ролей у впливі на стан авторегуляції тонусу мозкових артерій [40][41][42].…”
Section: український журнал серцево-судинної хірургії 2019unclassified